Recursos educacionais inclusivos em vídeos para pessoas com deficiência auditiva: protocolo de avaliação - NEVES, Fernanda Fonseca (2024)
Hearing loss has significantly affected people's lives, especially in the educational sphere, where the lack of accessibility and understanding of the specific needs of deaf people has been a constant challenge. Inclusive education has been essential to guarantee equal opportunities and a better quality of life for these people. Communication and accessibility barriers have hindered the learning and inclusion of these people in the digital educational environment. In this sense, the research aimed to identify the aspects that promote accessibility in inclusive elements of educational video resources for deaf people through an evaluation protocol, considering a) defining the elements of accessibility for deaf people in the educational context, b) proposing evaluation procedures for educational video resources with accessibility elements and c) validating the protocol for evaluating inclusive elements of educational video resources for deaf people. In this way, this study developed and validated an accessibility evaluation protocol for educational videos aimed at deaf people, focusing on three main categories: Libras, Subtitles and Visual Narratives. Using a qualitative and quantitative approach, videos from courses available on the Mtur and UNA-SUS platforms were analyzed. The protocol was applied to evaluate aspects such as the position, size, legibility and contrast of the subtitles, the quality of the translations into Libras and the structure of the visual narratives. The analysis revealed that although the videos presented a logical structure and some level of adequate contrast in the visual narratives, there were significant deficiencies in the Libras and Subtitles categories. The Libras windows often had problems with visibility and size, while the subtitles lacked adequate size and efficient contrast. The visual narratives also had problems with the contrast and size of the subtitles. Validation of the protocol showed that it was effective in identifying these problems and providing recommendations for improvement. The study concluded that the protocol developed was a valuable tool for analyzing accessibility in educational videos. The research highlighted the need for ongoing improvements in accessibility practices, including adjustments to the size and position of subtitles and Libras windows, and improvements to the contrast of visual narratives. The validation of the protocol confirmed its effectiveness and relevance, highlighting the importance of clear guidelines and continuous training of specialists. The work has made a significant contribution to the field of Information Design and accessibility, promoting more inclusive and equitable practices in the digital educational environment.